Drospondin, a glial glycoprotein with similarities to human Reelin/F-spondin, contributes to Drosophila brain development and function - Francisca Rojo-Cortés; Candy Roa-Siegfried; Paula Amado-Hinojosa; Nicolás Fuenzalida-Uribe; María-Constanza González-Ramírez; Raúl Chacón-Álvarez; Isidora Almonacid-Torres; Serge Birman; Lindsey D. Goodman; Oguz Kanca; Carlos Oliva; María Paz Marzolo; et al. (Proceedings of the National Academy of Sciences, 2026)
Reelin is a secreted glycoprotein with roles in the development of the mammalian neocortex, hippocampus, and cerebellum. This vertebrate signaling molecule also contributes to adult brain function. Mammalian Reelin increases the complexity of Drosophila Mushroom Body (MB) neurites, an effect mediated by LpR1 and LpR2, the orthologs of mammalian Reelin receptors. Paradoxically, to date, no Reelin ortholog has been described in Drosophila . Here, we report that the protein product of the uncharacterized Drosophila CG17739 gene, which we named Drospondin, shares sequence homology with vertebrate F-spondin and Reelin. We show that Drospondin is expressed in glial cells and is crucial for MB development. Our results also show that Drospondin genetically interacts with LpRs and that human Reelin rescues neuronal and brain structural defects in Drospondin-deficient flies. Furthermore, Drospondin-deficient flies exhibit altered sleep, locomotion, and social behaviors. Our results reveal that Drospondin is a Drosophila protein with similar functions to mammalian Reelin/F-spondin, that has an essential role in brain development and function, the impairment of which has profound functional consequences for the animal.